Cyclic AMP‐regulated opposing and parallel effects of serotonin and dopamine on phototaxis in the Marmorkrebs (marbled crayfish). (23rd July 2017) - Shiratori, Chihiro; Suzuki, Nanoka; Momohara, Yuto; Shiraishi, Kyosuke; Aonuma, Hitoshi; Nagayama, Toshiki
Abstract: Phototactic behaviours are observed from prokaryotes to amphibians and are a basic form of orientation. We showed that the marbled crayfish displays phototaxis in which the behavioural response reversed from negative to positive depending on external light conditions. Animals reared in a 12‐L/12‐D light cycle showed negative phototaxis during daytime and positive phototaxis during night‐time. Animals reared under constant light conditioning showed negative phototaxis during day‐ and night‐time, while animals reared under constant dark conditioning showed positive phototaxis during day‐ and night‐time. Injection of serotonin leads to a reversal of negative to positive phototaxis in both light/dark‐reared and light/light‐reared animals while injection of dopamine induced reversed negative phototaxis in dark/dark‐reared animals. Four hours of dark adaptation were enough for light/dark‐reared animals to reverse phototaxis from negative to positive. Injection of a serotonin 5HT1 receptor antagonist blocked the reverse phototaxis while serotonin 5HT2 receptor antagonists had no effects. Similarly, dark/dark‐reared animals reversed to showing negative phototaxis after 4 h of light adaptation. Injection of a dopamine DA1 receptor antagonist blocked this reverse phototaxis, while dopamine DA2 receptor antagonists had no effects. Injection of a cAMP analogue into light/dark‐reared animals blocked reverse phototaxis after dark adaptation, while adenylate cyclase inhibitor in dark/dark‐reared animals blocked reverse phototaxis after light adaptation. These results strongly suggest that serotonin mediates positive phototaxis owing to decreased cAMP levels, while dopamine‐mediated negative phototaxis occurs due to increased cAMP levels. Supporting this, the ratio of serotonin to dopamine in the brain was much higher in dark/dark‐reared than light/dark‐reared animals. Abstract : The sign of phototaxis in marbled crayfish could be reversed depending on external light conditions. Crayfish showed negative phototaxis under light conditions but positive phototaxis under dark conditions. cAMP was responsible for this switch in phototaxis. Dopamine injection induced negative phototaxis via the DA1 receptor and increased cAMP concentration, while serotonin induced positive phototaxis via the 5HT1 receptor and decreased cAMP levels.